Adequacy of Information Systems Programs: An Evaluation of Pedagogical Projects and Syllabi in Brazilian Higher Education - Romeiro, Bruna Oliveira; Caprino, Giancarlo Malfate; Joioso, Amanda Valukas Breviglieri; Barbosa, Ellen Francine (Anais do Workshop sobre Educação em Computação (WEI); 2025: Anais do XXXIII Workshop sobre Educação em Computação, 2025)
Higher Education Institutions (HEIs) must continuously adapt their curricula to meet market demands. This study examines Information Systems (IS) education in Brazilian HEIs, identifying gaps in program alignment with regulatory and scientific guidelines. An exploratory content analysis was conducted using quantitative and qualitative methods in Syllabi and Pedagogical Projects. The study aimed to identify how interdisciplinarity, competency-based learning, and the graduate profile are being addressed in IS programs. Findings indicate that while HEIs comply with regulations, curricula require updates to integrate competency-based education and interdisciplinary approaches recommended by scientific societies. The study contributes to discussions on IS education in Brazil, offering insights for future research and policy development.